The Validity of Boarding House Rental Agreements from Civil Law Perspectives - Rachman, Rahmia (Alauddin Law Development Journal (ALDEV), 2024)
Tenants of boarding houses generally make rental agreements informally; in fact, the situation tends to be weak, so legal protection is needed. The purpose of the research is to determine the validity of the room rental agreement and to understand the legal protection for tenants of boarding houses. The research method used in this study is normative juridical. The results of the study indicate that the validity of the room rental agreement is valid and binding on the parties if the agreement meets the requirements for a valid contract based on Article 1320 of the Civil Code, even if it is in an unwritten form. Legal protection for tenants of boarding houses includes preventive legal protection, paying the rental price and returning the room in good condition. Repressive legal protection applies if there is loss or damage in the boarding room caused by the negligence of the tenant.